Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Sensitization of primary cultures from rat dorsal root ganglia with lipopolysaccharide (LPS) requires a robust inflammatory response - Franz Nürnberger; Stephan Leisengang; Daniela Ott; Jolanta Murgott; Rüdiger Gerstberger; Christoph Rummel; Joachim Roth (Inflammation Research, 2022)
Objective We investigated whether it is possible to induce a state of “LPS-sensitization” in neurons of primary cultures from rat dorsal root ganglia by pre-treatment with ultra-low doses of LPS. Methods DRG primary cultures were pre-treated with low to ultra-low doses of LPS (0.001–0.1 µg/ml) for 18 h, followed by a short-term stimulation with a higher LPS-dose (10 µg/ml for 2 h). TNF-α in the supernatants was measured as a sensitive read out. Using the fura-2 340/380 nm ratio imaging technique, we further investigated the capsaicin-evoked Ca 2+ -signals in neurons from DRG, which were pre-treated with a wide range of LPS-doses. Results Release of TNF-α evoked by stimulation with 10 µg/ml LPS into the supernatant was not significantly modified by pre-exposure to low to ultra-low LPS-doses. Capsaicin-evoked Ca 2+ -signals were significantly enhanced by pre-treatment with LPS doses being above a certain threshold. Conclusion Ultra-low doses of LPS, which per se do not evoke a detectable inflammatory response, are not sufficient to sensitize neurons (Ca 2+ -responses) and glial elements (TNF-α-responses) of the primary afferent somatosensory system.

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

Manifestation of lipopolysaccharide-induced tolerance in neuro-glial primary cultures of the rat afferent somatosensory system - Franz Nürnberger; Stephan Leisengang; Daniela Ott; Jolanta Murgott; Rüdiger Gerstberger; Christoph Rummel; Joachim Roth (Inflammation Research, 2021)
Objective Bacterial lipopolysaccharide (LPS) may contribute to the manifestation of inflammatory pain within structures of the afferent somatosensory system. LPS can induce a state of refractoriness to its own effects termed LPS tolerance. We employed primary neuro-glial cultures from rat dorsal root ganglia (DRG) and the superficial dorsal horn (SDH) of the spinal cord, mainly including the substantia gelatinosa to establish and characterize a model of LPS tolerance within these structures. Methods Tolerance was induced by pre-treatment of both cultures with 1 µg/ml LPS for 18 h, followed by a short-term stimulation with a higher LPS dose (10 µg/ml for 2 h). Cultures treated with solvent were used as controls. Cells from DRG or SDH were investigated by means of RT-PCR (expression of inflammatory genes) and immunocytochemistry (translocation of inflammatory transcription factors into nuclei of cells from both cultures). Supernatants from both cultures were assayed for tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) by highly sensitive bioassays. Results At the mRNA-level, pre-treatment with 1 µg/ml LPS caused reduced expression of TNF-α and enhanced IL-10/TNF-α expression ratios in both cultures upon subsequent stimulation with 10 µg/ml LPS, i.e. LPS tolerance. SDH cultures further showed reduced release of TNF-α into the supernatants and attenuated TNF-α immunoreactivity in microglial cells. In the state of LPS tolerance macrophages from DRG and microglial cells from SDH showed reduced LPS-induced nuclear translocation of the inflammatory transcription factors NFκB and NF-IL6. Nuclear immunoreactivity of the IL-6-activated transcription factor STAT3 was further reduced in neurons from DRG and astrocytes from SDH in LPS tolerant cultures. Conclusion A state of LPS tolerance can be induced in primary cultures from the afferent somatosensory system, which is characterized by a down-regulation of pro-inflammatory mediators. Thus, this model can be applied to study the effects of LPS tolerance at the cellular level, for example possible modifications of neuronal reactivity patterns upon inflammatory stimulation.

Primary culture of the rat spinal dorsal horn: a tool to investigate the effects of inflammatory stimulation on the afferent somatosensory system - Stephan Leisengang; Franz Nürnberger; Daniela Ott; Jolanta Murgott; Rüdiger Gerstberger; Christoph Rummel; Joachim Roth (Pflügers Archiv - European Journal of Physiology, 2020)
One maladaptive consequence of inflammatory stimulation of the afferent somatosensory system is the manifestation of inflammatory pain. We established and characterized a neuroglial primary culture of the rat superficial dorsal horn (SDH) of the spinal cord to test responses of this structure to neurochemical, somatosensory, or inflammatory stimulation. Primary cultures of the rat SDH consist of neurons (43%), oligodendrocytes (35%), astrocytes (13%), and microglial cells (9%). Neurons of the SDH responded to cooling (7%), heating (18%), glutamate (80%), substance P (43%), prostaglandin E 2 (8%), and KCl (100%) with transient increases in the intracellular calcium [Ca 2+ ] i . Short-term stimulation of SDH primary cultures with LPS (10 μg/ml, 2 h) caused increased expression of pro-inflammatory cytokines, inflammatory transcription factors, and inducible enzymes responsible for inflammatory prostaglandin E 2 synthesis. At the protein level, increased concentrations of tumor necrosis factor-α (TNFα) and interleukin-6 (IL-6) were measured in the supernatants of LPS-stimulated SDH cultures and enhanced TNFα and IL-6 immunoreactivity was observed specifically in microglial cells. LPS-exposed microglial cells further showed increased nuclear immunoreactivity for the inflammatory transcription factors NFκB, NF-IL6, and pCREB, indicative of their activation. The short-term exposure to LPS further caused a reduction in the strength of substance P as opposed to glutamate-evoked Ca 2+ -signals in SDH neurons. However, long-term stimulation with a low dose of LPS (0.01 μg/ml, 24 h) resulted in a significant enhancement of glutamate-induced Ca 2+ transients in SDH neurons, while substance P-evoked Ca 2+ signals were not influenced. Our data suggest a critical role for microglial cells in the initiation of inflammatory processes within the SDH of the spinal cord, which are accompanied by a modulation of neuronal responses.

Microseismic events on the Åknes rockslide in Norway located by a back-projection approach - Tomáš Fischer; Daniela Kühn; Michael Roth (Journal of Seismology, 2020)

Neurons and astrocytes of the chicken hypothalamus directly respond to lipopolysaccharide and chicken interleukin-6 - Niklas Grabbe; Bernd Kaspers; Daniela Ott; Jolanta Murgott; Rüdiger Gerstberger; Joachim Roth (Journal of Comparative Physiology B, 2020)
In 4–5-month-old chicken, intravenous injections of bacterial lipopolysaccharide (LPS) induced a dose-dependent fever response and a pronounced increase of circulating interleukin-6 (IL-6). To assess a possible role for IL-6 in the brain of birds, a hypothalamic neuro-glial primary culture from 1-day-old chicken was established. Each well of cultured hypothalamic cells contained some 615 neurons, 1350 astrocytes, and 580 microglial cells on average. Incubation of chicken hypothalamic primary cultures with 10 or 100 µg/ml LPS induced a dose-dependent release of bioactive IL-6 into the supernatant. Populations of hypothalamic neurons (4%) and astrocytes (12%) directly responded to superfusion with buffer containing 10 µg/ml LPS with a transient increase of intracellular calcium, a sign of direct cellular activation. Stimulation of hypothalamic cultures with buffer containing 50 ng/ml chicken IL-6 induced calcium signaling in 11% of neurons and 22% of astrocytes investigated. These results demonstrate that IL-6 is produced in the periphery and in the hypothalamus in response to LPS in chicken. The observed cellular responses of hypothalamic cells to chicken IL-6 indicate that this cytokine may readily be involved in the manifestation of fever in the avian hypothalamus.

Diet effects in the asthma treatment: A systematic review - Gabriele Carra Forte; Daniela Terezinha Richter da Silva; Maria Luiza Hennemann; Roberta Aquiar Sarmento; Jussara Carnevale Almeida; Paulo de Tarso Roth Dalcin (Critical Reviews in Food Science and Nutrition, 2018)